Influence of the acoustic-structural couplings upon free vibrations of mechanical systems - HORÁČEK, J.; ZOLOTAREV, I. (Archives of Acoustics, 1993)
The roles of acoustic-structural couplings in three entirely different aeroelastic systems are compared. The first system is a thin elastic cylindrical shell containing fluid in a coaxial annular duct, the second system is a thin plate vibrating in fluid near a rigid wall, and the third system is a simple single degree-of-freedom mechanical system, vibrating in contact with a confined volume of an acoustic medium. It is shown that the nature of the acoustic-structural coupling is identical in all the studied cases.